Optimising Multilateral Cooperation in Combating Cybercrime to Enhance National Vigilance (Jurnal Lemhannas RI, 2024)
Purpose: Cybercrime poses an escalating threat to national security, necessitating stronger multilateral cooperation to address cybersecurity governance gaps. This analysis examines how strategic collaboration, legal harmonisation, and intelligence-sharing enhance cyber resilience while identifying key challenges and opportunities in reinforcing national vigilance against cyber threats.Study Design/Methodology/Approach: A qualitative approach with a comprehensive literature review of primary and secondary sources provides a structured assessment. A SWOT analysis evaluates the strengths, weaknesses, opportunities, and threats in global cybercrime cooperation, while a deductive analytical approach refines cybersecurity models using contemporary empirical data. This methodological framework offers policy insights into the effectiveness of international cyber governance strategies.Findings: Multilateral cooperation strengthens cyber resilience by facilitating intelligence-sharing, legal alignment, and coordinated cyber defences. Countries with integrated cybersecurity frameworks exhibit stronger defensive capabilities. However, regulatory inconsistencies, trust deficits, and technological gaps hinder collaboration. Addressing these barriers requires harmonised cybersecurity policies, enhanced cyber diplomacy, and joint capacity-building initiatives to improve global cybersecurity governance.Originality/Value: The analysis advances cybersecurity governance research by integrating SWOT analysis and deductive reasoning to evaluate multilateral strategies. Unlike previous studies that focus on unilateral or regional cybersecurity policies, this research highlights globally adaptive frameworks that reinforce national security. The findings offer concrete policy recommendations for institutions such as ASEAN, ITU, and UNODC to implement harmonised cybersecurity models, ensuring sustainable international cooperation against emerging cyber threats.
Keywords: Cybercrime; Cybersecurity Governance; Legal Harmonisation; Multilateral Cooperation; National Vigilance